2012
DOI: 10.1007/s11033-012-1986-0
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation and expression profiles of the brain-derived neurotrophic factor (BDNF) and dopamine transporter (DAT1) genes in patients with schizophrenia

Abstract: Methylation and expression profile of CpG islands were examined in the promoters of the brain-derived neurotrophic factor (BDNF) and dopamine transporter (DAT1) genes. These are well known to be involved in the pathophysiology of psychiatric disorders such as schizophrenia. Genomic DNA was extracted from peripheral blood of 80 patients with schizophrenia and 71 healthy controls. Methylation pattern was studied by Methylation-Specific PCR. RNA expression analysis was done on extracted RNA from blood samples fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 25 publications
1
42
0
Order By: Relevance
“…Studies of the DNA methylation profiles of the CpG island of the BDNF gene have shown that this gene could be useful as a biomarker of major depression [13,28]. The BDNF gene has been implicated as a susceptible locus for addiction to multiple drugs of abuse, such as alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies of the DNA methylation profiles of the CpG island of the BDNF gene have shown that this gene could be useful as a biomarker of major depression [13,28]. The BDNF gene has been implicated as a susceptible locus for addiction to multiple drugs of abuse, such as alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…This transporter is encoded by the SLC6A3 gene [13,31]. Recent studies have indicated that epigenetic mechanisms are directly involved in the molecular mechanisms that influence the genetic events that are involved in development as well as in the heritability of addiction to drugs of abuse [32,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next we examined genome-wide variation between the saliva and blood sample sets in genomic regions annotated to the following features: proximal promoters (2 kb upstream of RefSeq genes), RefSeq genes, coding sequences (CDS), LINEs (L1 and L2), SINEs (Alu), previously reported mental disorder-associated genes found by DNA methylation studies using peripheral tissue (BDNF, SLC6A4, CACNA1C, HTR1A, COMT, ST6GALNAC1, DRD2, and GAD1) [8,[67][68][69][70][71][72][73][74][75], and the above described DMWs. A box whisker plot of read counts in the grouped datasets at each genomic feature and a matching line graph for the individual datasets (normalized and summarized) showed a very similar profile with little variability and inter-individual difference, with DMWs as the natural exception ( Figure 4A,B).…”
Section: Comparable Dna Methylation Patterns Between Blood and Salivamentioning
confidence: 99%